Structure-based design and characterization of novel fusion-inhibitory lipopeptides against SARS-CoV-2 and emerging variants - Danwei Yu; Yuanmei Zhu; Tao Jiao; Tong Wu; Xia Xiao; Bo Qin; Huihui Chong; Xiaobo Lei; Lili Ren; Sheng Cui; Jianwei Wang; Yuxian He (Emerging Microbes and Infections)
The ongoing pandemic of COVID-19, caused by SARS-CoV-2, has severely impacted the global public health and socio-economic stability, calling for effective vaccines and therapeutics. In this study, we continued our efforts to develop more efficient SARS-CoV-2 fusion inhibitors and achieved significant findings. First, we found that the membrane-proximal external region (MPER) sequence of SARS-CoV-2 spike fusion protein plays a critical role in viral infectivity and can serve as an ideal template for design of fusion-inhibitory peptides. Second, a panel of novel lipopeptides was generated with greatly improved activity in inhibiting SARS-CoV-2 fusion and infection. Third, we showed that the new inhibitors maintained the potent inhibitory activity against emerging SARS-CoV-2 variants, including those with the major mutations of the B.1.1.7 and B.1.351 strains circulating in the United Kingdom and South Africa, respectively. Fourth, the new inhibitors also cross-inhibited other human CoVs, including SARS-CoV, MERS-CoV, HCoV-229E, and HCoV-NL63. Fifth, the structural properties of the new inhibitors were characterized by circular dichroism (CD) spectroscopy and crystallographic approach, which revealed the mechanisms underlying the high binding and inhibition. Combined, our studies provide important information for understanding the mechanism of SARS-CoV-2 fusion and a framework for the development of peptide therapeutics for the treatment of SARS-CoV-2 and other CoVs.